METODE PENGAJARAN MANTRA PADAANAK USIA DINI - Muratni, Ni Wayan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2017)
Hindus believe that life is overwhelmed and overcome by mantras. All beings are governed by a mantra, whether a farmer or a king. The mantra is composed using certain characters and arranged in such a way as to form a sound form, while the letters are the symbol of the sound. The mantra is described as a very subtle form or a subtle body of something, eternal and is an indestructible formula and is the origin of all non-eternal forms. Mantra can be sattvam, rajas, and tamas according to human character. Mantra can be given to young children to form the foundation of their lives. Teaching by using mantras in early childhood can be done by getting used to recite mantras when beginning and ending lessons, greetings when meeting with older people and others. The mantra taught is short and in the form of sattvam spells, which participate in building the children’s mental and character.